2015
DOI: 10.3109/08941939.2015.1088603
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Attenuates Inflammation in Experimentally Induced Acute Pancreatitis-Associated Lung Injury

Abstract: Oral Apigenin administration in rats, following experimental induced acute pancreatitis, seems to be protective on the lung tissue. Apigenin administration to humans could potentially ameliorate acute lung injuries. However, special caution is required for humans' use, as more detailed studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Thus, the protective effects of UTI on rat lung injury were associated with proteins of the TLR4/MyD88/NF-κB signaling pathway. Discussion 9 ALI, as a common clinical respiratory critical disease, is pulmonary parenchyma injury mainly caused by the interaction of inflammatory mediators and effector cells [21]. At present, effective therapies are still lacking in clinical practice, so it is imperative to seek prevention and treatment measures.…”
Section: Effects Of Uti On Protein Expressions Of Tlr4 Myd88 and Nf-κb In Lung Tissue Of Lps-induced Ratsmentioning
confidence: 99%
“…Thus, the protective effects of UTI on rat lung injury were associated with proteins of the TLR4/MyD88/NF-κB signaling pathway. Discussion 9 ALI, as a common clinical respiratory critical disease, is pulmonary parenchyma injury mainly caused by the interaction of inflammatory mediators and effector cells [21]. At present, effective therapies are still lacking in clinical practice, so it is imperative to seek prevention and treatment measures.…”
Section: Effects Of Uti On Protein Expressions Of Tlr4 Myd88 and Nf-κb In Lung Tissue Of Lps-induced Ratsmentioning
confidence: 99%
“…The most beneficial aspect of these phytochemicals is the lack of side effects. Therefore, in search of more treatment options for SAP associated ALI, researchers have tested several phytochemicals such as resveratrol [65] and apigenin [66] in experimental models and these phytochemicals have revealed promising protective potential for the treatment of SAP associated ALI.…”
Section: Phytocompounds Used For Treatment Of Sap Associated Lung Infmentioning
confidence: 99%
“…Results indicate improvement of lung tissue damage following apigenin administration. Apigenin reduces most histopathological alterations of the pulmonary tissue and decreases MPO and TNF-α activity [66].…”
Section: Apigeninmentioning
confidence: 99%
“…Studies have shown that children with different degrees of obesity have different degrees of glucose and lipid metabolism disorders. In these cases, as the degree of obesity increases, glucose and lipid metabolism disorders become more aggravated[ 1 ]. Insulin resistance (IR) refers to a decrease in the body's sensitivity to insulin, a decrease in the ability of insulin to lower blood sugar, and an obstacle to the use of glucose by tissues[ 2 ].…”
Section: Introductionmentioning
confidence: 99%